2014
DOI: 10.1177/0306624x14547033
|View full text |Cite
|
Sign up to set email alerts
|

Does Change in Hostility Predict Sexual Recidivism?

Abstract: The purpose of the study was to examine whether scores on a widely used measure of hostility--the Buss-Durkee Hostility Inventory (BDHI)--and change on this measure predicted sexual recidivism in a sample of 120 adult male incarcerated sexual offenders. Pre- and posttreatment scores, simple difference scores, and clinically significant change were examined. The majority of participants had functional scores on the BDHI prior to treatment. Of those who had dysfunctional pretreatment scores, the majority remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(112 reference statements)
0
2
1
Order By: Relevance
“…As expected, patients who were characterized by higher levels of impulsivity and hostility at the time of unconditional release were more likely to violently reoffend up to 5 years from release, which is in line with previous research (Douglas & Skeem, 2005;Spreen et al, 2014). However, in previous studies, the link between hostility and recidivism was mainly determined in a sample of sexual offenders (Firestone et al, 2005;Pettersen et al, 2015), while the current study demonstrates this relationship also in a sample of violent offenders. Moreover, the results showed that influence of risky network members is the strongest predictor Note.…”
Section: Discussioncontrasting
confidence: 46%
“…As expected, patients who were characterized by higher levels of impulsivity and hostility at the time of unconditional release were more likely to violently reoffend up to 5 years from release, which is in line with previous research (Douglas & Skeem, 2005;Spreen et al, 2014). However, in previous studies, the link between hostility and recidivism was mainly determined in a sample of sexual offenders (Firestone et al, 2005;Pettersen et al, 2015), while the current study demonstrates this relationship also in a sample of violent offenders. Moreover, the results showed that influence of risky network members is the strongest predictor Note.…”
Section: Discussioncontrasting
confidence: 46%
“…In general, studies published during the years following these reviews have utilized higher--quality methodologies, yet findings have remained decidedly inconsistent. For example, among studies examining change in sex offenders attending rehabilitation, one study reported that change scores predicted recidivism beyond static risk scores (Beggs & Grace, 2011), but this finding is balanced by non-significant results in both large sample (Barnett, Wakeling, Mandeville--Norden, & Rakestrow, 2013;Wakeling, Beech, & Freemantle, 2013) and small sample programs (Nunes, Pettersen, Hermann, Looman, & Spape, 2014;Pettersen et al, 2015;Woessner & Schwedler, 2014). Similarly, Olver, Kingston, Nicholaichuk, and Wong (2014) found only a few subscales predicted recidivism in their sample of sex offenders, while most pre--post measures did not; however, change in sexual deviance was a consistent predictor across two samples (Olver, Beggs Christofferson, et al, 2014).…”
Section: Meta--reviews Of Intra--individual Change During Rehabilitationmentioning
confidence: 99%
“…Although it is not their primary purpose, psychological treatment programs where risk assessments are completed before and after treatment are well-suited to this kind of research. Studies that have taken this approach have found some support for the hypothesis that reassessment improves prediction, with post-treatment dynamic assessment scores demonstrating stronger or incremental predictive validity over pre-treatment scores (Beggs & Grace, 2010;de Vries Robbé, de Vogel, Douglas, & Nijman, 2015;Hudson, Wales, Bakker, & Ward, 2002;Pettersen et al, 2015;Wakeling, Beech, & Freemantle, 2013). However, the effects have not been strong, and a meta-analysis of attitudes supportive of sexual offending, (Helmus, Hanson, Babchishin, & Mann, 2013), found no significant difference in the predictive accuracy of assessment scores from before and after treatment.…”
Section: Pre-and Post-treatment Designsmentioning
confidence: 99%